Sustainable development issues as an important factorof the contemporary international relations - Abdukhalyk, Zh. R.; Kukeyeva, F. T. (International relations and international law Journal, 2016)
The world seems to be growing more unstable under the global economic crisis, ongoing ethnic conflicts and environmental disasters and irrational human use of natural resources. In addition to the negative impact of natural disasters on the environment, a destructive power has been arisen from the anthropogenic and technogenic phenomena, which jeopardize the safe development of future generations. Therefore a priority of the modern society is to find the ways for optimal solving of current natural and anthropogenic problems and achieve a long-term sustainable development. Sustainable development issues are vital and urgent problems for independent experts, because nowadays the world community faces devastating phenomena as poverty and overpopulation, climate change, disability of many states for rational distribution of natural resources etc.